2017
DOI: 10.1590/1678-4499.095
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization in top dressing for wheat crop in succession to soybean under a no-till system

Abstract: Agricultural intensification to improve wheat yield has increased the demand for nitrogen fertilizers. This study aimed to investigate the wheat response in succession to soybean due to application of nitrogen rates and sources in top dressing, as well as to determine the N rates of maximum technical yield (MTY) and maximum economic yield (MEY). A field experiment was carried out in Ponta Grossa, Paraná State, Brazil, on a clayey Typic Hapludox

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
3
5
0
Order By: Relevance
“…Increasing the N rate did not change the P-grain concentration, in all wheat-cropping seasons, and increased the K-grain concentration only for wheat grown after maize in 2015. Even though the improvements in P and K plant nutrition with the N rates applied in top dressing were slight, a synergistic effect of both N × P and N × K interactions may have occurred in our study, especially for P in maize (Table 4) and K in wheat (Table 5), as reported in other studies (Los Galetto et al, 2017;Rufty, MacKown, & Israel, 1990). In addition, the increase in N provided by top-dressing fertilization may have favored plant root growth (Caires, Zardo Filho, Barth, & Joris, 2016;Xue et al, 2014) and increased P and K uptake due to increased soil volume exploration by roots.…”
Section: Amendment Effects On Soil and Plant Nutritionsupporting
confidence: 75%
See 1 more Smart Citation
“…Increasing the N rate did not change the P-grain concentration, in all wheat-cropping seasons, and increased the K-grain concentration only for wheat grown after maize in 2015. Even though the improvements in P and K plant nutrition with the N rates applied in top dressing were slight, a synergistic effect of both N × P and N × K interactions may have occurred in our study, especially for P in maize (Table 4) and K in wheat (Table 5), as reported in other studies (Los Galetto et al, 2017;Rufty, MacKown, & Israel, 1990). In addition, the increase in N provided by top-dressing fertilization may have favored plant root growth (Caires, Zardo Filho, Barth, & Joris, 2016;Xue et al, 2014) and increased P and K uptake due to increased soil volume exploration by roots.…”
Section: Amendment Effects On Soil and Plant Nutritionsupporting
confidence: 75%
“…In addition, N translocation from leaves to grains is high. Several studies conducted under NT systems in Brazil have shown an increase in N‐leaf concentration of maize (Caires & Milla, 2016; Soratto, Silva, Cardoso, & Mendonça, 2011) and wheat (Los Galetto et al., 2017; Teixeira Filho, Buzetti, Andreotti, Arf, & Sá, 2011) with increasing N rate application. In grains, an increase in N concentration was also obtained with top dressing N fertilization compared to N application only at sowing of maize (Pedrosa et al., 2020) and with increasing N rate application in top dressing of wheat (Los Galetto et al., 2017; Rodrighero et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In our study conducted on an Oxisol with 35 g dm −3 of organic matter in the topsoil (Table 1), a rate of 55 kg N ha −1 for wheat cultivar Quartzo following soybean provided a maximum economic return to obtain grain yield of 4250 kg ha −1 . Similar results under a soybean-wheat system were found in other studies, with wheat responding economically to the rate of 35 kg N ha −1 for yield around 3100 kg ha −1 [38], and to the rate of 61.5 kg N ha −1 for yield around 4000 kg ha −1 [17]. It is true that to provide more appropriate N recommendations for wheat, our study should have comprised more cultivars, soils, locations, and years.…”
Section: Effect Of N Fertilization On Wheat Shoot Dry Matter and Graisupporting
confidence: 84%
“…Based on the regression equation for grain yield (Fig. 2b) Since the soil N availability is dependent on mineralization of organic matter [5] and due to the essential role of N in high-yield systems [7], positive effects of N fertilization on wheat yields have been frequently observed in studies conducted on Brazilian soils [11,17,28]. In our study conducted on an Oxisol with 35 g dm −3 of organic matter in the topsoil (Table 1), a rate of 55 kg N ha −1 for wheat cultivar Quartzo following soybean provided a maximum economic return to obtain grain yield of 4250 kg ha −1 .…”
Section: Effect Of N Fertilization On Wheat Shoot Dry Matter and Graimentioning
confidence: 99%
“…Wheat (Triticum aestivum) is one of the most important crops in the maintaining of the security of the food supply and is the second most consumed cereal worldwide (Galetto et al, 2017;Franco et al, 2018;Oliveira and Pinto-Maglio, 2017). Drought is one of the main constraints affecting wheat production, and is found in virtually all climatic regions, providing a huge challenge to local farming in many countries worldwide (Lobell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%